Special Needs Dental Management of the Class 3 Obese Patient. (10th February 2019) - Malik, Zanab
Abstract : Obesity, classified as a chronic disease by the World Health Organisation (WHO), is a worldwide public health problem. Obesity has links with numerous systemic diseases which may complicate dental management and as such, patients with obesity and concomitant medical comorbidities are commonly managed by Special Needs Dentistry specialist departments in Australia. The sparsity of available evidence on the dental status in this group is likely due to significant access issues experienced by the class 3 obese, who often weigh >140 kg and therefore are unable to be examined or treated in conventional dental chairs. "Bariatric" is a term used to refer to a specific branch of medicine dealing with causes, prevention, and treatment of obesity. It is used widely in the literature to refer to obese patients; however, dentistry for this cohort ("bariatric dentistry") is less well defined and represents less frequently used terminology. This case report is of a 58-year-old female, with class 3 obesity, who presented in May 2018 for outpatient consult to the Special Needs Unit/Medically Complex Dental Clinic at Westmead Centre for Oral Health, Sydney, Australia, with a compromised and neglected dentition and requiring full dental clearance. The case highlights many of the significant access issues and considerations for safe and effective delivery of dental management. As we move into the future, dental professionals need to become more aware of the growing challenge obesity presents and understand how medical complexities influence dental management. Facilities need to be able to meet this growing need and the specific requirements for a functional and safe bariatric dental service; dependent on both appropriate infrastructure and training.